Revitalisasi Produk Tempe dalam Wisata Edukasi Keberlanjutan Melalui Hilirisasi Karpet Interaktif Muatan Pembelajaran Berbasis Game dan Model Pembelajaran Problem Based Learning - Eka Putri Surya; Abdul Rahman Prasetyo; Adinda Marcelliantika; Alby Aruna; Ginanjar Atma Wijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The revitalization of tempe products in sustainable educational tourism through the downstreaming of interactive carpets with game-based learning content and Problem Based Learning (PBL) models aims to enhance attractiveness and learning effectiveness. This program integrates interactive technology and problem-based learning approaches to create enjoyable and immersive educational experiences. Methods include developing game-based interactive carpets, providing technical training for tourism managers, and evaluating effectiveness through user feedback. Results indicate increased learning interest and visitor understanding of tempe production processes and sustainability concepts. The implementation of this program is expected to support the development of innovative educational tourism and promote environmental sustainability.